Understanding the representational dimension of learning: the implications of interactivity, immersion and fidelity on the development of serious games - de Freitas, Sara; Dunwell, I. (Nova Science Publishers, 2011)
Modern interactive digital mediums enable educational content to be represented in increasingly varied and Modern interactive digital mediums enable educational content to be represented in increasingly varied and sophisticated ways. An increasingly popular way of conveying this content is through ‘serious games’ – games created through a careful balance of modern entertainment game technology with instructional design concepts and pedagogies. The rapid emergence of this educational medium has proven particularly challenging for designers, who must achieve this balance in the face of few proven design approaches. de Freitas and Oliver (2006) advocate a ‘four-dimensional’ approach to this design challenge; coupled with a participatory approach which advocates involvement from learners in early stages of the development process, this model has provided a design framework for a number of serious games including Triage Trainer and Patient Rescue.This chapter explores in more depth the ‘representation’ dimension of this framework. It is described as comprising of three aspects which together provide for immersive and interactive 3D virtual environments for training and learning applications. The main components of the representational dimension are discussed within this chapter as including interactivity with aspects of user control and selection, feedback and affect, immersion, with aspects of narrative and flow, and levels of fidelity, with higher fidelity levels often being associated with greater ease of learning transfer. Consequently, this chapter outlines a sub-theory of the four dimensional framework which seeks to frame a set of metrics that can be used to measure game and virtual world efficacy, and which may inform aspects of serious game mechanics and design.Having defined in more detail the elements that constitute an effective representation of serious game content, this chapter applies it for validation into three diverse case study areas: Triage Trainer, the Rome Reborn project and Re-Mission. The three case studies set a context for discussion regarding the representation of serious games, and highlight some of the key issues and challenges associated with game-based learning and serious game design. Ultimately, this chapter raises questions serious game developers commonly face: to what level does content need to be represented to effectively realise pedagogies, and what gains can be achieved from investment in novel technology?